With One Voice: Elements of Acclamation in Early Jewish Liturgical Poetry - Lieber, Laura Suzanne (Harvard theological review, 2018)
In this essay, the Rosh Hashanah Shofar service poems by the Jewish poet Yose ben Yose (fourth or fifth century CE, Land of Israel) are read through the lens of the Late Antique practice of acclamation. Yose's surviving body of works is limited, but he was influential within the Jewish tradition, and his poems have long been noted for their use of formal features such as fixed-word repetitions and refrainsfeatures which align not only with poetic norms from the biblical period to Late Antiquity but also with the practice of acclamation. Jews attended (and performed in) the theater and games; they were familiar with rhetorical and oratorical training and related literary norms; and they were integrated socially, commercially, and politically into diverse and varied communities. The affinity of Jewish liturgical poetry from antiquity for other forms of poetic composition reflects Jews' general embeddedness in Late Ancient culture. Reading Yose's poetry as shaped by the conventions of acclamation highlights how Yose and his congregants were not only distinctly Jewish but also thoroughly Roman.